Front Pages IJReSES Vol. 13, No. 1(2016) - Editorial Journal (BRIN, 2016)
Front Pages IJReSES Vol. 13, No. 1(2016) Â Â *Note:Â This cover is a revision version of theÂ Editorial Committee Preface section cover that was uploaded on May 26, 2017